2014
DOI: 10.1371/journal.pone.0107275
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation of GSTT1 and GSTM1 and the Risk of Prostate Cancer in a Caribbean Population of African Descent

Abstract: BackgroundDeletions of the glutathione S-transferase genes M1 and T1 (GSTM1 and GSTT1) have been studied as potential risk factors for prostate cancer. Conflicting results have been obtained. Moreover, most such studies could not discriminate heterozygous from homozygous carriers of the non-deleted alleles.ObjectiveWe investigated whether copy number variation (CNV) of the GSTM1 and/or GSTT1 genes contribute to the risk of prostate cancer in the Caribbean population of African descent of Guadeloupe.MethodsIn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 27 publications
(38 reference statements)
3
11
0
1
Order By: Relevance
“…However, it is unclear if glutathione conjugation of acrylamide occurs non-enzymatically or through catalyzation by GSTs 12 . Interestingly, regardless of acrylamide intake, women with a double deletion of GSTM1 were at a decreased risk of endometrial cancer in our study, which has been observed before 13 , and also for some other cancers 14 15 . A possible explanation is that GSTs catalyze the conjugation of reduced glutathione (GSH) to compounds that protect against endometrial cancer or that they bioactivate compounds involved in endometrial carcinogenesis, for instance catechol estrogens 16 .…”
Section: Discussionsupporting
confidence: 69%
“…However, it is unclear if glutathione conjugation of acrylamide occurs non-enzymatically or through catalyzation by GSTs 12 . Interestingly, regardless of acrylamide intake, women with a double deletion of GSTM1 were at a decreased risk of endometrial cancer in our study, which has been observed before 13 , and also for some other cancers 14 15 . A possible explanation is that GSTs catalyze the conjugation of reduced glutathione (GSH) to compounds that protect against endometrial cancer or that they bioactivate compounds involved in endometrial carcinogenesis, for instance catechol estrogens 16 .…”
Section: Discussionsupporting
confidence: 69%
“…The deletion of a CNV at 2p24.3 also increases prostate cancer risk and furthermore, it confers aggressive characteristics on prostate cancer (OR = 1.31) [69]. In addition to these CNVs, a CNV at 22q11.23 including gene GSTT1affects the risk of prostate cancer; two and 3 or more copies of GSTT1 increase the risk of prostate cancer with odds ratios of 1.55 and 4.89, respectively [70].…”
Section: Prostate Cancermentioning
confidence: 99%
“…However, other factors also deserve to be investigated, including: 1) increased rates of smoking, particularly in women; 2) Changes in lifestyle and eating habits that have led to a high rate of obesity, a known risk factor for cancer, especially colorectal cancer; 3) Environmental pollution by pesticides, particularly chlordecone, which warrants further research in cancer sites other than the prostate; 4) The role of oncogenic infectious agents also deserves investigation, such as the human papillomavirus and its genotypes circulating in the Caribbean, which are associated with a high risk of cervical cancer; as well as also Helicobacter pylori and the risk of stomach cancer. These factors may be implicated in the pathogenesis or exacerbation of these cancers [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%